2005
DOI: 10.1002/j.1839-4655.2005.tb00979.x
|View full text |Cite
|
Sign up to set email alerts
|

The Right of Young People to be Heard

Abstract: In 1993 the New Zealand Government ratified the United Nations Convention on the Rights of the Child. It placed a reservation against Article 32 maintaining that legislation of a minimum age for entry into employment would not be in the best interests of children. The Government is reconsidering this reservation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Legislation of minimum working ages often is seen as a means of reducing exploitation of young people, but it is not supported by young people themselves (Bourdillon et al, 2010;Leonard, 2004). A survey of around 1500 New Zealand school students found that most enjoyed their work and did not want the government to legislate a minimum age for paid employment; of those who did, most suggested their own age or younger as a minimum (Gasson, 2005).…”
Section: Consequences Of Age Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Legislation of minimum working ages often is seen as a means of reducing exploitation of young people, but it is not supported by young people themselves (Bourdillon et al, 2010;Leonard, 2004). A survey of around 1500 New Zealand school students found that most enjoyed their work and did not want the government to legislate a minimum age for paid employment; of those who did, most suggested their own age or younger as a minimum (Gasson, 2005).…”
Section: Consequences Of Age Limitationsmentioning
confidence: 99%
“…In their respective reports to the UN Committee on the Rights of the Child, Australia and New Zealand have questioned whether a blanket minimum age is in the best interests of young people. Like the governments of Australia and New Zealand, young people and their families question the merit of blanket minimum-age legislation (Bourdillon et al, 2010;Gasson, 2005). Young people view themselves as holders of rights, including rights to respect, to have their views taken seriously (Taylor and and to education and safe work (Beals and Zam, 2010;Bourdillon et al, 2010;Gasson, 2005;Leonard, 2002Leonard, , 2004Liebel, 2003).…”
Section: Legislation On Young People's Employmentmentioning
confidence: 99%
See 1 more Smart Citation